Selecting the Best Power Generation Technologies by Using Multi Criteria Decision Making Analysis - Dweib, Hadeel; Melhem, Yousef (Journal of Palestine Ahliya University for Research and Studies, 2024)
The increasing demand for electric power is prompting engineers to consider sustainable energy production systems in Europe. Challenges include energy supply security, affordability, material efficiency, and environmental protection. Based on a number of variables, this study seeks to determine which sustainable technologies are most effective for producing electricity. Numerous competing criteria are present in the sources of energy production; multi-criteria decision-making methods (MCDM) were applied, and the analysis was conducted using the MULTIMOORA, VIKOR, and TOPSIS methodologies. The results of the MULTI MOORA method revealed the best biomass (CHP) power plants; via VIKOR, the best technology for producing electricity was condensing turbine coal; and for TOPSIS, the best technology was solar photovoltaics. These findings demonstrated that future energy policy should be focused on sustainable energy technologies.